Development of natural gum based fast disintegrating tablets of glipizide - Jha, Antesh Kumar; Chetia, Dipak (Asian Journal of Pharmaceutics (AJP), 2014)
Dysphagia and risk of choking are leading causes of patient nonâ€compliance in the selfâ€administration of conventional tablets.To overcome these limitations of conventional tablets fastâ€disintegrating tablets were developed, using natural gums.Natural gums were evaluated for bulk swelling capacity. Powder mix containing natural gums and glipizide was evaluated for water sorption, swelling index and capillary action. For faster onset and immediate hypoglycemic action, the fast disintegrating tablets were prepared with various types of natural gums using the direct compression technique. Formulations containing guar gum disintegrated within a minute and fulfilled the official requirements for dispersible tablets. As the amount of guar gum increased, the friability increased and hardness decreased, resulting in a shorter wetting and disintegration time. Gum acacia and gum tragacanth did the opposite.The glipizideâ€loaded fast disintegrating tablet prepared with 18 mg of guar gum gave a friability of 0.46 Â± 0.02%, content uniformity of 99.34 Â± 0.82%, drug content of 99.15 Â± 1.16%, wetting time of 39.0 Â± 1.04 sec, hardness of 5.70 Â± 1.41 Kg and disintegration time less than 30 sec, suggesting that it was a practical product with a good tablet property. In conclusion, natural gum based patientâ€friendly fast disintegrating tablets of glipizide can be successfully formulated.